How interview questions are placed in time influences caregiver description of social communication symptoms on the ADI‐R. (22nd September 2014) - Jones, Rebecca M.; Risi, Susan; Wexler, Diana; Anderson, Deborah; Corsello, Christina; Pickles, Andrew; Lord, Catherine
<x xml:space="preserve">Abstract</x> Background Caregiver report is crucial for the diagnosis of childhood onset psychiatric disorders, particularly autism. Three experiments were conducted to determine whether caregiver reports of past and current behaviors are affected by question timing and ordering. Methods Using the Autism Diagnostic Interview – Revised (ADI‐R), two studies systematically varied the order in which caregivers were asked about behaviors. In a third study, descriptions of children's current behaviors at age 5 were compared to retrospective descriptions of behaviors at age 5 collected at age 10. Results Caregivers, who were first asked about a history of symptoms, described less severe past and present behavior than caregivers reporting current behaviors as well as caregivers reporting current and history of symptoms together. Caregivers retrospectively reported more severe behaviors for age 5 when their children were age 10 than they had when their children were age 5. Conclusions Caregivers describe past behaviors differently depending on whether they are asked about current symptoms first. Methods of caregiver reporting can influence interpretations of symptom severity with effects on diagnoses and research findings.